2013
DOI: 10.3329/bjsir.v48i1.15408
|View full text |Cite
|
Sign up to set email alerts
|

In vitro clonal multiplication of Aegle marmelos (L.) Corr. through cotylodonary node culture

Abstract: Clonal multiplication of Aegle marmelos was achieved through in vitro culture. Cotyledonary nodes from one month old in-vitro grown seedlings of Aegle marmelos were cultured on MS medium supplemented with BAP, Kn, and IBA either alone or in combination. The highest regenerative response was observed on medium containing 2.5 mg/L BAP and 0.5 mg/L Kn from node and shoot tip within 8-10 days. When regenerated shoots were subcultured on MS medium supplemented with 0.2 mg/L BAP and 0.02 mg/L Kn, maximum number of m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
1
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 5 publications
4
1
0
Order By: Relevance
“…They observed that MS without the addition of any auxin was sufficient for the establishment of in vitro rooting of G. procumbens. Morimoto et al (1994), Cuenca and Amo-Marco (2000), Akter et al (2013), obtained the similar result in case of Salvia miltiorrhiza, Salvia bancoana and Salvia valentine, respectively and in Aegle marmelos. The maximum rooting response (100%) of Gynura procumbens was achieved on MS supplemented with NAA (0.5 mg/l) according to Parvin et al (2014).…”
Section: Resultssupporting
confidence: 66%
“…They observed that MS without the addition of any auxin was sufficient for the establishment of in vitro rooting of G. procumbens. Morimoto et al (1994), Cuenca and Amo-Marco (2000), Akter et al (2013), obtained the similar result in case of Salvia miltiorrhiza, Salvia bancoana and Salvia valentine, respectively and in Aegle marmelos. The maximum rooting response (100%) of Gynura procumbens was achieved on MS supplemented with NAA (0.5 mg/l) according to Parvin et al (2014).…”
Section: Resultssupporting
confidence: 66%
“…1f-g). Similar effects were also observed in different other plants (Akter et. al., 2013;Islam et al, 2010;Jaheduzzaman et al, 2012;Khan et al, 2016).The increased amount of decomposed cow dung enriched Nitrogen (N) phosphorus (P), Potasium (K) in soil (Ewulo et al, 2007) which are responsible for root induction of Chrysanthemum (Budiarto and Sulyo, 2013).…”
Section: Resultssupporting
confidence: 89%
“…In addition, low concentration of IBA (<1.0 mg/l) and less time (< 5 minutes) soaked of cut end decreased the percentages and number of root induction. The effect of IBA solution to introduce root induction of different woody plants has been published elsewhere (Paul and Aditi, 2009;Cai et al 2007;Akter et al, 2013;Khan et al, 2012;Islam et al, 2010) and this investigation also supported their works. In vitro rooting was achieved in medium containing 1.0 mg/l IBA by Siham (2016).…”
Section: Resultssupporting
confidence: 82%
“…2b) both proved to be most suitable for root induction within 15-20 days. Similar effect also found in previous study (Zakaria et al 2014,Husaini and Srivastava 2011,Sakila et al 2007, Akter et al 2013.On the other hand, Zakaria et alreported MS medium containing1.5 mg/l NAA revealed the highest percentage of forming root. Ko et al reported that roots were successfully formed at low concentrations of NAA (0.02mg/l).…”
Section: Sterilants and Their Combinationsupporting
confidence: 84%